The diversity of the top management team and the survival and success of international companies: The case of Spanish companies with foreign direct investment in China - Niñerola, Angels; Hernández-Lara, Ana Beatriz; Sánchez-Rebull, Maria Victòria (Revista Internacional de Organizaciones, 2016)
There is an important stream of research in internationalisation studies about the influence of governing bodies on organisational expansion strategies. Using Upper Echelon Theory, this paper aims to analyse how the diversity of the top management team affects the success and survival of the company abroad. Data were collected from Spanish companies with foreign direct investment in China during the period 2012-2013. China was chosen as the host country because it is the world's largest recipient of FDI and because of the considerable cultural and geographical differences between China and Spain, which make the investments especially risky and uncertain. Therefore, it deserves additional research. The results indicate that a top management team with members of very different ages has a negative impact on the success of the company abroad because the generational differences introduce different opinions into decision-making process. However, gender diversity increases the survival of the company. Survival is also greater if the company is smaller because it is more flexible and has a greater ability to adapt to market contingencies.